Analisis Kesalahan Siswa dalam Menyelesaikan Permasalahan Sistem Persamaan Linear Dua Variabel - Hilza Karyawati Indriani; Dedy Juliandri Panjaitan (Universitas Indraprasta PGRI Jakarta, 2021)
The purpose of this research is to find out the errors and factors that cause student errors during working on the SPLDV. This research uses a qualitative with a qualitative descriptive type of research. The research subjects were all students of class VIII A MTs Persiapan Negeri of Tagor Island Village, and selected 3 students as interview subjects. The research instrument consisted of a written test and an unstructured interview. The results of the analysis were found, 4 students getting predicate B made a few mistakes with a value range of 84-92 fulfilling the KKM, it was found that 8 students getting predicate C and D made a lot of mistakes with a value range of 75-83 and <75 scores below the KKM. The conclusion of the study was that there were 95.65% conceptual errors and 86.95% errors in principle and operation. Factors that cause errors are: not understanding the concept, only focusing on the examples given by the teacher. do not master algebraic operations. careless in answering questions.